The Effect of Earning Per Share, Leverage, Liquidity, Company Size and Age on Stock Price - Setyana, Elya Nur; Nurcahyono, Nurcahyono (Economics and Business International Conference Proceeding, 2024)
This study aims to determine the effect of earning per share, leverage, liquidity, company size, and company age on stock price in technology sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The population in this study is technology sector companies in the software & it services subsector listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. This research method uses a purposive sampling technique. With the sample used, a total of 14 technology companies that met the criteria were sampled and 42 data were obtained. The data used is secondary data obtained through documentation. The analysis used in this study is multiple linear regression analysis using the SPSS version 26 calculation tool. Based on the results of this study, it shows that earning per share, leverage, liquidity, company size and company age have a positive effect on stock price.